2019
DOI: 10.4103/ijri.ijri_109_18
|View full text |Cite
|
Sign up to set email alerts
|

Conventional and magnetic resonance hysterosalpingography in assessing tubal patency—A comparative study

Abstract: Context: Tubal factors, one of the leading causes of female infertility, have been conventionally evaluated by hysterosalpingography (HSG). The role of magnetic resonance imaging (MRI) in assessing female infertility is gaining importance because of its inherent efficiency in detecting structural abnormalities. Magnetic resonance hysterosalpingography (MR HSG) is less invasive and avoids exposure of ovaries to ionizing radiation. Its utility is extrapolated to visualize fallopian tubes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Currently, various techniques are employed to assess fallopian tubal patency of the tubes, including X-ray hysterosalpingography (HSG) ( 6 , 7 ), hysterosalpingo-contrast sonography (HyCoSy) ( 8 , 9 ), magnetic resonance hysterosalpingography (MR-HSG) ( 10 ), hysteroscopic tubal cannulation ( 11 ), and laparoscopic chromopertubation (LC) ( 12 ). Although LC has been acknowledged as the reference test, HyCoSy has been adopted as one of the first-line options for evaluating infertility due to its simplicity and high diagnostic performance ( 6 , 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, various techniques are employed to assess fallopian tubal patency of the tubes, including X-ray hysterosalpingography (HSG) ( 6 , 7 ), hysterosalpingo-contrast sonography (HyCoSy) ( 8 , 9 ), magnetic resonance hysterosalpingography (MR-HSG) ( 10 ), hysteroscopic tubal cannulation ( 11 ), and laparoscopic chromopertubation (LC) ( 12 ). Although LC has been acknowledged as the reference test, HyCoSy has been adopted as one of the first-line options for evaluating infertility due to its simplicity and high diagnostic performance ( 6 , 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…• Pain due to catheterization, to contrast injection in the uterine cavity or to the need of higher pressure when trying to unblock the tube (pain can persist in the following hours, so that resting and oral analgesics are recommended) None of the adverse effects above were seen in our study, except for pain. Jagganatan et al in 2019 [19] confirmed how sensibility, specificity, positive and negative predictive value and diagnostic accuracy in tubal patency were absolutely comparable between the two techniques and that there were no statistically significant differences. This is in accordance with our study because our results are completely overlapping in the assessment of unilateral and bilateral tubal patency.…”
Section: Discussionmentioning
confidence: 94%
“…None of the adverse effects above were seen in our study, except for pain. Jagganatan et al in 2019 [ 19 ] confirmed how sensibility, specificity, positive and negative predictive value and diagnostic accuracy in tubal patency were absolutely comparable between the two techniques and that there were no statistically significant differences. This is in accordance with our study because our results are completely overlapping in the assessment of unilateral and bilateral tubal patency.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that pelvic MRI is an inevitable tool in infertility evaluation, and MR-HSG can be used in addition as it avoids exposure of the reproductive organs to radiation and has the same efficacy as X-HSG. [ 8 ] Li YZ et al had studied that Compared with the conditional X-HSG (the imaging gold standard), the pooled sensitivity, specificity, positive likelihood ratio, negative likelihood ratio, diagnostic odds ratio and the area under the curve of MR-HSG for tubal occlusion were 0.91 (95% CI: 0.48–0.99), 1.00 (95% CI: 0.87–1.00), 230.47 (95% CI: 6.79–7824.72), 0.09 (95% CI: 0.01–0.80), 2676.10 (95% CI: 61.35–120000), and 1.00 (95% CI: 0.99–1.00), respectively. Subgroup analyses revealed that viscosity of contrast agent ( P = .024) and test order ( P = .036) affected the accuracy of MR-HSG to evaluate tubal occlusion.…”
Section: Introductionmentioning
confidence: 99%
“…Jagannathan D et al had assessed that the diagnostic accuracies of MR-HSG and conventional X-ray HSG (X-HSG) in identifying tubal patency in women with infertility. They concluded that pelvic MRI is an inevitable tool in infertility evaluation, and MR-HSG can be used in addition as it avoids exposure of the reproductive organs to radiation and has the same efficacy as X-HSG [8] . Li YZ et al had studied that Compared with the conditional X-HSG (the imaging gold standard), the pooled sensitivity, specificity, positive likelihood ratio, negative likelihood ratio, diagnostic odds ratio and the area under the curve of MR-HSG for tubal occlusion were 0.91 (95% CI: 0.48–0.99), 1.00 (95% CI: 0.87–1.00), 230.47 (95% CI: 6.79–7824.72), 0.09 (95% CI: 0.01–0.80), 2676.10 (95% CI: 61.35–120000), and 1.00 (95% CI: 0.99–1.00), respectively.…”
Section: Introductionmentioning
confidence: 99%